Gambling problems and help-seeking in serving United Kingdom military personnel: A qualitative study - Champion, Hannah; Pritchard, Amy; Dighton, Glen; Dymond, Simon (Frontiers in Psychiatry, 2022)
Military personnel are vulnerable to gambling problems, yet many are reluctant to seek help. The aim of the current study was to explore the lived experience of problem gambling and help-seeking among serving members of the United Kingdom Armed Forces. Seventeen individuals from a larger, cross-sectional survey of gambling and wellbeing in the Royal Air Force (RAF) completed semi-structured interviews. Interview questions focused on personal experiences, the context of the RAF and its influence, knowledge and experiences of treatment and support services, and the impact of COVID-19. Reflexive thematic analysis revealed 4 themes: 1) harmful and protective occupational factors; 2) socio-cultural and personal influences; 3) organisational attitudes towards mental health and help-seeking, and 4) current support pathways and provision. Findings also indicated that alcohol use and gambling are common within the RAF, and that personnel are actively coping with mental health challenges.